Corporeidade, saúde e cultura: o sentido do Sesc como espaço educativo para crianças e jovens - Valério, Alan Luis Vieira (2023)
Questioning about the meaning of Sesc as an educational space for children and young people, taking into account the practices related to body health, this work aims to investigate the educational actions of the Curumim and Juventudes programs in the Sesc Campo Limpo unit, through transversality between corporeity, cultural plurality and the promotion of the health of children and young people. The methodology used is predominantly qualitative through a bibliographic survey and field research through a questionnaire to analyze educational activities from the point of view of educators, having as theoretical references Paulo Freire, HérnandezHérnandez and Sancho-Gil, Michel Foucault, Carlos Botazzo, Hugo Assmann, among others. The data obtained in this research revealed that children and young people from the Curumim and Juventudes programs find at Sesc Campo Limpo a space for freedom of expression and knowledge socialization, whose epistemological curiosity is present in order to lead them to reflect and discuss critically on issues pertaining to corporeity and health. Educational actions are based on promoting dialogue and listening, encouraging intergenerational coexistence and valuing the plurality of ideas, experiences and experiences, providing a pleasurable, dynamic and fun educational activity. The planning of educational actions includes the precepts of the rhizomatic curriculum or "rizocurriculum", in which educators reflect and conceive their activities aligned to an open, modifiable, adaptable, flexible and connectable curriculum with all those involved in the process (students, managers, local community and multiple knowledge). In this way, the students were able to develop and share their multiple potentialities in favor of acquiring knowledge elaborated by a collective and collaborative way, always in motion, in continuous construction, marked by experimentation and affections, horizontal and non-hierarchical relationships of coexistence, evidenced for its heterogeneity and infinite possibilities of connection, reaffirming the sense of Sesc as a space of education for all those who experience and share its environments and activities